Komparasi Kurikulum Bahasa Arab di Masa Orde Baru dan Reformasi dalam Lintasan Sejarah - Khusen, Rahmad; Fadlilah, Nurul; Abadi, Ma'ruf; Adnan, Luthfi; Mizan, Ahmad Nur (Study Program of Arabic Language Teaching, 2025)
This study aims to conduct an in-depth comparison of the orientation and focus of the Arabic Language Curriculum during the New Order and Reform eras, and to identify the implications of this paradigm shift. This study is a qualitative descriptive research that applies a historical study and library research approach, where data is collected through documentation and relevant curriculum literature. The gathered data is analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing stages.The results of this comparison reveal a fundamental difference in the curricular orientation between the two eras. The Arabic language curriculum during the New Order period (including the 1968, 1975, 1984, and 1994 curricula) was essentially focused on the theological-scientific aspect, or utilizing it as a receptive tool for understanding religious texts (the Qur'an and Hadith), with a primary emphasis on grammatical elements (nahwu-sharaf) through a partial approach. Conversely, the curriculum during the Reform era (covering the 2004 KBK, 2006 KTSP, 2013 K13, up to the current Independence Curriculum) reflects a sharp shift in focus to become more sociological-communicative and competency-based. The curriculum in this era demands mastery of comprehensive language skills (listening, speaking, reading, and writing) and aims functionally to meet the communication demands of the global society. This shift indicates that the Reform curriculum is more adaptive and provides greater room for the development of students' productive skills.